Neutrophil gelatinase‐associated lipocalin level is a prognostic factor for survival in rat and human chronic liver diseases. Issue 9 (16th October 2017) - Yoshikawa, Kyoko; Iwasa, Motoh; Eguchi, Akiko; Kojima, Shinichi; Yoshizawa, Naohiko; Tempaku, Mina; Sugimoto, Ryosuke; Yamamoto, Norihiko; Sugimoto, Kazushi; Kobayashi, Yoshinao; Hasegawa, Hiroshi; Takei, Yoshiyuki
Abstract : Chronic liver disease patients often have complications, such as hepatocellular carcinoma (HCC) and acute bacterial infection. Model for end‐stage liver disease and Child‐Pugh scores are useful prognostic factors for chronic liver diseases but not for all chronic conditions, such as HCC. Our investigative aim targeted the prognostic abilities of neutrophil gelatinase‐associated lipocalin (NGAL) in rat and human chronic liver diseases. Blood NGAL levels were measured by enzyme‐linked immunosorbent assay in rats with cirrhosis and 96 patients with chronic liver disease and HCC. We examined the correlation between blood NGAL levels and liver functions as well as survival. In our rat model, liver NGAL expression was assessed by immunostaining, real‐time quantitative polymerase chain reaction, and immunoblot. In rats with cirrhosis, blood NGAL levels were continuously and significantly elevated in the deceased group and were significantly correlated with liver functions. Liver NGAL, toll‐like receptor 4, and interleukin‐6 levels were increased in the deceased group compared to the survival group. Blood NGAL levels were significantly correlated with liver NGAL levels, indicating blood NGAL was derived from the liver. In patients with chronic liver disease, blood NGAL levels were associated with liver function and renal function. Blood NGAL levels were significantly increased in patients with chronic liver disease with HCC compared to without HCC. For the survival group, 38 out of 96 patients were dead in the average follow‐up period of 9.9 months. The patients with blood NGAL ≤119 ng/mL had significantly longer rates of survival compared to patients with blood NGAL >119 ng/mL. Conclusion : Blood NGAL predicts the survival rate in rat and human chronic liver diseases. Our findings suggest blood NGAL may be prognostic of survival in chronic liver diseases complicated by HCC. ( Hepatology Communications 2017;1:946–956)